Shikonin Induces ROS-Dependent Apoptosis Via Mitochondria Depolarization and ER Stress in Adult T Cell Leukemia/Lymphoma - Piyanard Boonnate; Ryusho Kariya; Seiji Okada (Antioxidants, 2023)
Adult T cell leukemia/lymphoma (ATLL) is an aggressive T-cell malignancy that develops in some elderly human T-cell leukemia virus (HTVL-1) carriers. ATLL has a poor prognosis despite conventional and targeted therapies, and a new safe and efficient therapy is required. Here, we examined the anti-ATLL effect of Shikonin (SHK), a naphthoquinone derivative that has shown several anti-cancer activities. SHK induced apoptosis of ATLL cells accompanied by generation of reactive oxygen species (ROS), loss of mitochondrial membrane potential, and induction of endoplasmic reticulum (ER) stress. Treatment with a ROS scavenger, N-acetylcysteine (NAC), blocked both loss of mitochondrial membrane potential and ER stress, and prevented apoptosis of ATLL cells, indicating that ROS is an upstream trigger of SHK-induced apoptosis of ATLL cells through disruption of the mitochondrial membrane potential and ER stress. In an ATLL xenografted mouse model, SHK treatment suppressed tumor growth without significant adverse effects. These results suggest that SHK could be a potent anti-reagent against ATLL.